2018
DOI: 10.2147/opth.s151313
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous intratunnel cross-linking with intrastromal corneal ring segment implantation versus simultaneous epithelium-off cross-linking with intrastromal corneal ring segment implantation for keratoconus management

Abstract: PurposeThe purpose of this study is to compare the efficacy of intratunnel cross-linking combined with intrastromal corneal ring segment (ICRS) implantation versus combined epithelium-off (epi-off) cross-linking and ICRS implantation for the management of keratoconus.MethodsOur study included 20 eyes of 12 patients with moderate-to-severe keratoconus. Group A included 10 eyes that underwent simultaneous ICRS implantation with intratunnel cross-linking. Group B included 10 eyes that underwent simultaneous ICRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A huge number of published works are devoted to the investigation of the efficacy and safety of combined methods in the treatment of keratoconus [ 1 , 5 , 6 , 12 , 16 , 28 ]. Coshkunseven et al reported an efficacy and safety of combined treatment, including posterior chamber toric phakic Visian ICL implantation after Keraring ICRS implantation followed by CXL in a three-step procedure in 14 keratoconic eyes with extreme myopia and astigmatism [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A huge number of published works are devoted to the investigation of the efficacy and safety of combined methods in the treatment of keratoconus [ 1 , 5 , 6 , 12 , 16 , 28 ]. Coshkunseven et al reported an efficacy and safety of combined treatment, including posterior chamber toric phakic Visian ICL implantation after Keraring ICRS implantation followed by CXL in a three-step procedure in 14 keratoconic eyes with extreme myopia and astigmatism [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hosny et al presented the comparative results of two variations of combined surgical treatment in keratoconus, including different CXL types: a combination of intra-tunnel CXL with ICRS implantation and a combination of epithelium-off CXL with ICRS in 20 eyes. Simultaneous intra-tunnel CXL with implantation of ICRS showed early visual rehabilitation due to the absence of epithelial defect [ 5 ]. Our observation gave possibility to compare efficacy of the independent application of CXL or ICRS with the use of their combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, intratunnel ICRS plus CXL can induce earlier improvements in UDVA and CDVA, as well as mean K and Kmax reduction compared to epithelium-off cross-linking with ICRS implantation owing to the absence of epithelial defects. [ 33 ] Interestingly, combining ICRS implantation and CXL in a single, same-day session can reduce keratometry values than the consecutive procedures. [ 34 ] Seemingly, the newly dissected corneal channel created by femtosecond laser may enhance riboflavin pooling, leading to substantial corneal flattening.…”
Section: Discussionmentioning
confidence: 99%